2015
DOI: 10.1016/j.gerinurse.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness meditation in older adults with postherpetic neuralgia: A randomized controlled pilot study

Abstract: This parallel-group, randomized controlled pilot study examined daily meditation in a diverse sample of older adults with postherpetic neuralgia. Block randomization was used to allocate participants to a treatment group (n = 13) or control group (n = 14). In addition to usual care, the treatment group practiced daily meditation for six weeks. All participants completed questionnaires at enrollment in the study, two weeks later, and six weeks after that, at the study’s end. Participants recorded daily pain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…Five (Brown and Jones, 2013;la Cour and Petersen, 2015;Ljotsson, Falk, et al, 2010;Rahmani and Talepasand, 2015) of the 13 studies reporting mental health-related quality of life reported a significant effect, and this effect is significant in the pooled analysis (SMD 0.44; CI 0.18, 0.69; 13 RCTs; I 2 50.6%) (Brown and Jones, 2013;Gaylord et al, 2011;la Cour and Petersen, 2015;Ljotsson, Falk, et al, 2010;Meize-Grochowski et al, 2015;Morone, Greco and Weiner, 2008;Plews-Ogan et al, 2005;Rahmani and Talepasand, 2015;Teixeira, 2010;Wells et al, 2014). 1 Twelve studies measured physical health-related quality of life (Brown and Jones, 2013;Gaylord et al, 2011;la Cour and Petersen, 2015;Ljotsson, Falk, et al, 2010;Meize-Grochowski et al, 2015;Morone, Greco, and Weiner, 2008;Rahmani and Talepasand, 2015;Teixeira, 2010;Wells et al, 2014), and four of these studies used a remote intervention (Ljotsson, Falk, et al, 2010;Meize-Grochowski et al, 2015;Teixeira, 2010). 2 Three (Ljotsson, Falk, et al, 2010;Rahmani and Talepasand, 2015) of the 12 and all of those using a remote intervention report a significant positive effect of meditation on physical health-related quality of life.…”
Section: Health-related Quality Of Lifementioning
confidence: 94%
See 4 more Smart Citations
“…Five (Brown and Jones, 2013;la Cour and Petersen, 2015;Ljotsson, Falk, et al, 2010;Rahmani and Talepasand, 2015) of the 13 studies reporting mental health-related quality of life reported a significant effect, and this effect is significant in the pooled analysis (SMD 0.44; CI 0.18, 0.69; 13 RCTs; I 2 50.6%) (Brown and Jones, 2013;Gaylord et al, 2011;la Cour and Petersen, 2015;Ljotsson, Falk, et al, 2010;Meize-Grochowski et al, 2015;Morone, Greco and Weiner, 2008;Plews-Ogan et al, 2005;Rahmani and Talepasand, 2015;Teixeira, 2010;Wells et al, 2014). 1 Twelve studies measured physical health-related quality of life (Brown and Jones, 2013;Gaylord et al, 2011;la Cour and Petersen, 2015;Ljotsson, Falk, et al, 2010;Meize-Grochowski et al, 2015;Morone, Greco, and Weiner, 2008;Rahmani and Talepasand, 2015;Teixeira, 2010;Wells et al, 2014), and four of these studies used a remote intervention (Ljotsson, Falk, et al, 2010;Meize-Grochowski et al, 2015;Teixeira, 2010). 2 Three (Ljotsson, Falk, et al, 2010;Rahmani and Talepasand, 2015) of the 12 and all of those using a remote intervention report a significant positive effect of meditation on physical health-related quality of life.…”
Section: Health-related Quality Of Lifementioning
confidence: 94%
“…Ten studies were judged to be of fair quality, primarily due to being unclear in some aspects of the methods (Cash et al, 2015;Davis and Zautra, 2013;Day et al, 2014;Dowd et al, 2015;Gaylord et al, 2011;la Cour and Petersen, 2015;Morone, Greco, and Weiner, 2008;Wells et al, 2014). Eleven studies were judged to be poor; eight of these were primarily due to issues with completeness of reporting outcome data, such as inadequate or missing ITT analysis or less than 80-percent follow-up Brown and Jones, 2013;Cathcart et al, 2014;Esmer et al, 2010;Meize-Grochowski et al, 2015;Morone et al, 2009;Omidi and Zargar, 2014;PlewsOgan et al, 2005). Three studies were judged poor primarily due to unclear methods (Rahmani and Talepasand, 2015;Teixeira, 2010;Wong, 2009).…”
Section: Study Quality/risk Of Bias For Individual Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations